2017
DOI: 10.3389/fmicb.2017.02072
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus subtilis Biofilm Development – A Computerized Study of Morphology and Kinetics

Abstract: Biofilm is commonly defined as accumulation of microbes, embedded in a self-secreted extra-cellular matrix, on solid surfaces or liquid interfaces. In this study, we analyze several aspects of Bacillus subtilis biofilm formation using tools from the field of image processing. Specifically, we characterize the growth kinetics and morphological features of B. subtilis colony type biofilm formation and compare these in colonies grown on two different types of solid media. Additionally, we propose a model for asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 34 publications
1
30
0
Order By: Relevance
“…Similar to colonies grown on agar that lacks glycerol and manganese (non-biofilm-promoting, [21]), the nutrient-deprived colonies also demonstrated a more stable bacterial GFP signal production at their core with a smaller characteristic decrease of GFP signal over time ( Figure 3B). In both cases, the loss of complex wrinkled formations at the colony core was accompanied by a smaller decrease in the GFP signal produced by the bacterial cells at the colony core, supporting a previous suggestion that there is an inherent "cost" to the formation of the network of wrinkles in the long term [21].…”
Section: Bacterial Kineticsmentioning
confidence: 77%
See 1 more Smart Citation
“…Similar to colonies grown on agar that lacks glycerol and manganese (non-biofilm-promoting, [21]), the nutrient-deprived colonies also demonstrated a more stable bacterial GFP signal production at their core with a smaller characteristic decrease of GFP signal over time ( Figure 3B). In both cases, the loss of complex wrinkled formations at the colony core was accompanied by a smaller decrease in the GFP signal produced by the bacterial cells at the colony core, supporting a previous suggestion that there is an inherent "cost" to the formation of the network of wrinkles in the long term [21].…”
Section: Bacterial Kineticsmentioning
confidence: 77%
“…B. subtilis biofilms, for example, when grown under biofilm-promoting conditions, develop a complex network of such wrinkles but only at the colony core, not the periphery. Under standard biofilm-promoting conditions, the wrinkled structure is a reflection of the biofilm's elasticity [21]. Conversely, the channels that develop under nutrient-limiting conditions appear straight and span the entire colony from the center to the very edge of the biofilm.…”
Section: Biofilm Morphologymentioning
confidence: 99%
“…Bacilus subtilis growth kinetics and morphological features were characterized for colony type biofilm formation previously [ 64 ]. The complexity of B. subtillis biofilm is characterized by a rapidly developing three-dimensional complex structure with the core size remains largely unchanged while the colony expansion is mostly attributed to the growth in the area of outer cell subpopulations [ 65 ]. Oliveira et al [ 66 ] indicated that CAEOs were effective in controlling multi-species biofilms.…”
Section: Resultsmentioning
confidence: 99%
“…subtilis is a well-known model microorganism to study the molecular principles of biofilm development. B. subtilis growth kinetics and morphological features were characterized with a colony type biofilm formation [37]. Biofilm of B. subtillis is quickly developing into a three-dimensional complex structure with an unchanged core and expansion, which is mostly related to the outer cell subpopulations enlargement.…”
Section: Discussionmentioning
confidence: 99%